A Miniature Coxey's Army: The British Harvesters' Toronto-to-Ottawa Trek of 1924 - Cherwinski, W. J. C. (Walter Joseph Carl) (Labour / Le Travail, 1993)
A labor shortage in 1922, the promise of a bumper yield in 1923, and increased imperialist sentiment resulted in the recruitment of nearly 12,000 British workers to assist Canadian harvesters with the 1923 prairie wheat crop. Since most of them came from the cities they found the transition to western agriculture difficult and their complaints about the treatment they endured caused considerable damage to Canada's image abroad. Nevertheless, many persevered and returned home after the harvest satisfied. Those who remained to make a new life for themselves had a harder time since they were forced to take farm work at subsistence wages for the winter. Others chose to seek work in their own trades in Canada's cities. Like many, those in Toronto faced unemployment but, with the help of area radicals, the militants among them decided to lead a long march to demand work at reasonable wages from the Mackenzie King government. Despite unrelenting harassment from public officials they remained united and, with the assistance of citizens in the communities along the way, they reached the capital bedraggled but defiant a fortnight later. While their march proved futile in the short term, it was an early example of escalating militancy among the unemployed, both domestic and immigrant, which helped to focus attention on both the plight of unskilled labor in a national economy and on the short-sighted, employer-driven immigration policies.

Eugene Alfred Forsey, 1904-1991: Caring Canadian - Cherwinski, W. J. C. (Walter Joseph Carl) (Labour / Le Travail, 1991)
Pays homage to the life and work of Eugene Forsey, who for many years was the research director of the Canadian Congress of Labour/Canadian Labour Congress and later was appointed a senator by prime minister Pierre Elliott Trudeau. An influential advocate of the study of labour history, Forsey's book, "Trade Unions in Canada, 1812-1902," a standard reference work in the field, was the fruit of a CLC project of the 1960s, for which Canada Council funding was obtained to hire graduate students to assist with the research. Forsey also helped to obtain funding for the founding of the journal, Labour/Le Travail. A photo of Forsey is included.
Keywords: FORSEY; Eugene Alfred; 1904-1991; Obituaries

A Class Act: An Illustrated History of the Labour Movement in Newfoundland and Labrador - Cherwinski, W. J. C. (Walter Joseph Carl) (Labour / Le Travail, 1988)
This article reviews the book, "A Class Act: An Illustrated History of the Labour Movement in Newfoundland and Labrador," by Bill Gillespie.

Joseph Hugh Tuck, 1929-86: A Personal Tribute - Cherwinski, W. J. C. (Walter Joseph Carl) (Labour / Le Travail, 1987)
Pays homage to the life and work of Hugh Tuck, who taught labour history at Memorial University. Includes a list of significant publications and a photo.
Keywords: Joseph Hugh; TUCK

A Flannel Shirt and Liberty: British Emigrant Gentlewomen in the Canadian West, 1880-1914 - Cherwinski, W. J. C. (Walter Joseph Carl) (Labour / Le Travail, 1984)
This article reviews the book, "A Flannel Shirt and Liberty: British Emigrant Gentlewomen in the Canadian West, 1880-1914", edited by Susan Jackel.

Gentlemen Emigrants: From the British Public Schools to the Canadian Frontier - Cherwinski, W. J. C. (Walter Joseph Carl) (Labour / Le Travail, 1983)
This article reviews the book, "Gentlemen Emigrants: From the British Public Schools to the Canadian Frontier," by Patrick A. Dunae.

Alberta Labour: A Heritage Untold - Cherwinski, W. J. C. (Walter Joseph Carl) (Labour / Le Travail, 1981)
This article reviews the book, "Alberta Labour: A Heritage Untold," by Warren Caragata.

The Incredible Harvest Excursion of 1908 - Cherwinski, W. J. C. (Walter Joseph Carl) (Labour / Le Travail, 1980)
To satisfy the continuing need for agricultural labour in western Canada, especially at harvest time, the CPR after 1890 ran cheap harvest excursions from Eastern and central Canada each August and September. Accordingly, to insure an adequate supply of workers and potential settlers the railway companies, together with the federal and provincial governments, created an image of the prairies as a land of opportunity offering plentiful jobs at high wages. Owing to a variety of factors, however, unprecedented numbers responded to the 1908 appeal causing unexpected problems for all concerned. Some of those in the Maritime contingent were particularly troublesome as, bored and thirsty, they went on a rampage which touched most of the communities on the Main Line from Chalk River to Winnipeg. Once in the West distribution problems plagued all the excursionists with the result that places like Winnipeg, Moose Jaw, and Regina had too many harvesters on hand, while other places faced shortages. Consequently, numerous men wandered about aimlessly looking for work and often were forced to accept alternate employment at substantially less money than they had expected. The result was that the image of the West as capable of satisfying all those who went there in search of work was temporarily tarnished.

Organized Labour in Saskatchewan: The TLC [Trades and Labor Congress] Years, 1905-1945 - Cherwinski, W. J. C. (Walter Joseph Carl) (University of Alberta, 1972)
In view of the existence of a predominantly agricultural economy in the province of Saskatchewan, especially in the years before the Second World War, one might assume that the study of organized labour would lack significance. But the very presence of a movement from the beginning of the province, a movement which continued to exist and even grow, albeit slowly, was in itself important. ...It is one of the objectives of this project to examine the extent to which organized labour, usually considered a force of the left, compared with and contributed to this radical tradition. However, the largest part of this study, based essentially on a wide variety of manuscript sources, is concerned with the historical development of the movement in the years 1905 to 1945, the years dominated by the Trades and Labor Congress of Canada....

Lectures in Canadian Labour and Working-Class History - Cherwinski, W. J. C. (Walter Joseph Carl); Kealey, Gregory S.; Committee on Canadian Labour History (AU Press, 1985)
In 1983 and 1984 the Canadian Studies Program of the Secretary of State funded four lecture series at Canadian universities on the history of the Canadian working class. This volume presents many of the lectures in a published version. Ranging from east to west and covering two centuries of Canadian labour history, the volume includes a selection of essays by some of Canada's leading social historians including Michael Cross, David Frank, Ross McCormack, Bryan Palmer and Joy Parr. Outstanding participants in the making of Canadian labour history Eugene Forsey and H. Landon Ladd have also contributed. Directed at a popular audience these fourteen lectures provide a major survey of Canada's labour past. –Publisher's description
https://archive.org/details/lecturesincanadi0000unse http://www.aupress.ca/index.php/books/cclh01
Keywords: Canada; History; Labor; Labor Unions; Labor movement; Working class